Analysis of Traveling Wave and Combined Site Effect of Long-Span Upper-Bearing Concrete-Filled Steel Tubular Arch Bridge - Zite Li; Genhui Wang; Jiang Fan; Yue Jian; Yongliang Zhang (Advances in Civil Engineering)
In order to study the traveling wave effect and combined site effect of long-span steel tube concrete-filled arch bridge, a 400-m span bridge of the same type is taken as an example, and a large-mass time-history analysis method with multipoint input of recorded seismic waves is used. A total of 11 kinds of traveling wave excitations and 9 kinds of combined site excitations under 4 types of typical sites are carried out to calculate the structural response, and the chord axial force ratio and displacement changes are compared and analyzed. The results show that the long-span arch bridge also has nonuniform seismic excitation conditions in the lateral and vertical directions, and the spatial effect of the structural response is significant; under the traveling wave excitation, the change of the axial force ratio of the chord has a certain periodicity, and it is not the larger the axial force ratio is, the larger the axial force ratio is; the X direction has a significant influence, the maximum axial force ratio of the vault under the design condition is 6.26, and the changes in the Y and Z directions are relatively gentle, but there are still nearly two times the working condition; after the same amplitude modulation of different recorded waves, under the uniform excitation, the axial force is similar, but the displacement is quite different; under the unidirectional traveling wave excitation, the displacement in the X and Z directions shows an accelerating and increasing trend toward the vault. When it is relatively consistent under the unidirectional combined site excitation, and the axial force ratio changes under small and then increases, the L/4–3L/8 segment has a significant impact; the axial force ratio changes are the combined site excitation in different directions are spatially random; three under the combined site excitation. The axial force ratio in the orthogonal direction changes greatly. When the hard field is transformed into the soft field, the axial force ratio decreases, and the displacement increases continuously.